Comparison of Single and Dual Console Systems in the Robotic Surgical Training of Graduating Obstetrics and Gynecology Residents in the United States [103]. (May 2015) - Mikhail, Emad; Miladinovic, Branko; Bassaly, Renee; Hart, Stuart; Imudia, Anthony N.
Abstract : INTRODUCTION: The use of robotic surgical systems in gynecologic surgery is continuing to increase. The dual console system has the potential to improve resident participation and training in robotic-assisted surgeries. The goal of this study is to compare obstetrics and gynecology residents' self-assessment of surgical training on single and dual console robotic systems. METHODS: An anonymous survey was designed using Qualtrics web-based survey software. The survey link was sent to all graduating obstetrics and gynecology residents and program directors in the United States by e-mail. RESULTS: A total of 39 program directors and 34 residents completed the survey. Thirty-one (70%) program directors and 26 (70%) residents reported that the dual console is being utilized in their institution. Thirty-six percent of program directors report that residents performed more than 20 robotic-assisted total laparoscopic hysterectomy cases in the dual console group compared with only 13% in single console group ( P =.111), whereas 30% of residents in the dual console group report performing more than 20 robotic-assisted total laparoscopic hysterectomies compared with none in single console group ( P =.124). Programs with a dual console had higher rates of providing training certificates at graduation: 52% (dual console group) compared with 22% (single console group) reported by program directors ( P =.148) compared with 43% (dual console group) compared with 0% (single console group) reported by graduating residents ( P =.032). CONCLUSION: Dual consoles are utilized in 70% of obstetrics and gynecology residency programs that completed the survey. Utilization of a dual console significantly increased the rate of obtaining training certificates as reported by residents. Utilization of a dual console did not significantly increase the number of robotic-assisted total laparoscopic hysterectomy cases performed by residents as reported by residents and program directors.